Profitable partnerships: smallholders, industry, eucalypts and acacias in Asia. Issue 1 (2nd January 2022) - Arnold, R.; Midgley, S.; Stevens, P.; Phimmavong, S.; Kien, N. D.; Chen, S.
ABSTRACT: Smallholder tree-growers make substantial contributions to commercial wood flows in many countries in Asia. Many of these growers choose eucalypt and/or acacia species, which offer profitable and sustainable land-use options. Smallholder acacia and eucalypt plantings in India, Lao People's Democratic Republic, Sri Lanka, China, Thailand and Viet Nam are discussed, and data are presented to show the magnitude of these resources. In each country, smallholder plantings form critical raw-material inputs for numerous processors, with the collective scale of their wood production exceeding 86 million m 3 annually and worth over USD 2.4 billion annually directly to these growers. Such harvests are major contributors to the livelihoods of smallholder families and to the economic viability of numerous local wood-using industries that rely on the raw materials they generate. This paper describes the profitable partnerships in Asia between smallholder tree-growers and their eucalypts and acacias, discusses their species of choice and the consequences of such decisions, and explores how and why these partnerships have developed and endured.